Depth-Dependent Genetic Structuring of a Depth-Generalist Coral and Its Symbiodiniaceae Algal Communities at Campeche Bank, Mexico - Alexis B. Sturm; Ryan J. Eckert; Ashley M. Carreiro; Nuno Simões; Nuno Simões; Nuno Simões; Joshua D. Voss (Frontiers in Marine Science, 2022)
Depth-generalist coral holobionts inhabit shallow (0–30 m) and mesophotic (30–150 m) reef zones but may exhibit genetic specialization as a result of adaptations to environmental shifts and/or due to a lack of dispersal across depth. The level of depth-dependent genetic structuring varies across reef locations which may impact the roles mesophotic populations play in the persistence and recovery of metapopulations. A depth-generalist coral species, Montastraea cavernosa, was sampled across a shallow to mesophotic gradient at 10, 15, 25, and 35 m at Alacranes and Bajos del Norte reefs on Campeche Bank, Mexico. Both 2bRAD and ITS2 sequencing were used to quantify genetic differentiation of the coral hosts and community structure of their algal endosymbionts (Family Symbiodiniaceae) across depth zones and between these reefs. Significant levels of M. cavernosa genetic differentiation were identified across depth at both reefs, especially between the shallow (10, 15, and 25 m) and mesophotic (35 m) zones. While Symbiodiniaceae hosted by these corals were predominantly Cladocopium species, both depth and reef location were significant factors driving ITS2 type profiles found within each population. The magnitude of depth-dependent genetic structuring of both the coral and Symbiodiniaceae was much greater at Alacranes, relative to Bajos del Norte, suggesting that the refugia potential of mesophotic communities at Alacranes is limited. However, relatively high levels of horizontal coral connectivity between the two reefs, and Bajos del Norte’s location at the entrance to the Gulf of Mexico suggests that it may play an important role in the maintenance of the coral’s regional metapopulation and should be considered in future assessments of this species’ connectivity dynamics and management.